Organizational behavior - Schermerhorn, John R (Wiley, 2015)
Presents students with a portfolio of skills that enable them to thrive in whatever area of business they eventually choose. This title emphases on ethics, leadership, and sustainability - with the same organization, content, and cohesive voice that guides students in the right direction.